2016
DOI: 10.1038/srep18884
|View full text |Cite
|
Sign up to set email alerts
|

Onset of main Phanerozoic marine radiation sparked by emerging Mid Ordovician icehouse

Abstract: The Great Ordovician Biodiversification Event (GOBE) was the most rapid and sustained increase in marine Phanerozoic biodiversity. What generated this biotic response across Palaeozoic seascapes is a matter of debate; several intrinsic and extrinsic drivers have been suggested. One is Ordovician climate, which in recent years has undergone a paradigm shift from a text-book example of an extended greenhouse to an interval with transient cooling intervals – at least during the Late Ordovician. Here, we show the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
170
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(191 citation statements)
references
References 50 publications
18
170
1
2
Order By: Relevance
“…This nonlinear response suggests that the development of a large‐scale ice sheet during the Ordovician could have occurred in conjunction with a moderate tropical sea surface temperatures signal, the amplitude of which would be within the error bars of routine geochemical analyses [e.g., Finnegan et al , ] and thus potentially below the detection limits. This further implies that warm tropical Ordovician seas [ Trotter et al , ; Finnegan et al , ] and geological evidence for glacioeustatic events [ Loi et al , ; Turner et al , ; Dabard et al , ; Rasmussen et al , ] are not mutually exclusive (30.3°C at 12 PAL, Figure ). Interestingly, experiments using a lowered topography (section 3.3.1) are typified by a glacial onset occurring at 8 PAL (instead of 12 PAL).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This nonlinear response suggests that the development of a large‐scale ice sheet during the Ordovician could have occurred in conjunction with a moderate tropical sea surface temperatures signal, the amplitude of which would be within the error bars of routine geochemical analyses [e.g., Finnegan et al , ] and thus potentially below the detection limits. This further implies that warm tropical Ordovician seas [ Trotter et al , ; Finnegan et al , ] and geological evidence for glacioeustatic events [ Loi et al , ; Turner et al , ; Dabard et al , ; Rasmussen et al , ] are not mutually exclusive (30.3°C at 12 PAL, Figure ). Interestingly, experiments using a lowered topography (section 3.3.1) are typified by a glacial onset occurring at 8 PAL (instead of 12 PAL).…”
Section: Discussionmentioning
confidence: 99%
“…It is also still unclear how glacial onset could have possibly occurred in the midst of a prolonged period of hot climate. Evidence for warm shallow seas in the tropics (up to 37°C) [ Finnegan et al , ], as suggested by most recent Ordovician geochemical data [ Trotter et al , ; Finnegan et al , ], is in apparent contradiction with Middle to Upper Ordovician deposits where glacioeustatic events are identified [ Loi et al , ; Turner et al , ; Elrick et al , ; Dabard et al , ; Rasmussen et al , ] or suggested [ Nielsen , ] (see discussion in Amberg et al []). These eustatic cycles support the presence of ice sheets since the Middle Ordovician Darriwilian (467 Ma) rather than a sudden emplacement of a massive ice sheet restricted to the Hirnantian stage (445–444 Ma).…”
Section: Introductionmentioning
confidence: 99%
“…Correlation coefficients between series of proportional change (Δt/t-1) of subsampled diversity based on stratigraphic opinions with one-time bin versus two-time bin minimum resolution. Generalised differencing was used to reduce effects of autocorrelations (McKinney, 1990;Alroy, 2000;Novack-Gottshall and Miller, 2003 during the Darriwilian (Rasmussen et al 2016;Trubovitz and Stigall, 2016) …”
Section: Discussionmentioning
confidence: 99%
“…JLs-1 for carbonates: Rasmussen et al 2016). It is further encouraged to analyse element concentrations from a split of each sample solution for preservation control (Ullmann et al 2013(Ullmann et al , 2014Rasmussen et al 2016). …”
Section: Data Accuracy Comparability and Confidencementioning
confidence: 99%